The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00411-012-0421-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in furanocoumarin content and phenylalanine ammonia lyase activity in developing seedlings of Psoralea corylifolia L. in response to gamma irradiation of seeds

Abstract: Gamma irradiation of seeds is known to be an important factor in stimulating biochemical and physiological processes. The aim of the present study was to investigate phenylpropanoids and associated enzymes responsible for the production of active metabolites. Furanocoumarin content was estimated in seeds of Psoralea corylifolia L. during two successive generations (G(1) and G(2)) where as phenylalanine ammonia lyase (PAL) activity was measured in leaves at different developmental stages of P. corylifolia L. ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[7] also applied 2,4-D to determine the accumulation of anthocyanins in the cell culture of strawberries. 2,4-D appears to cause stress in plants and to increase the phenolic compounds synthesis [31,12] also reported that the medium supplemented with 2,4-D for the carrot callus initiation showed an increase in abscissic acid which resulted in a higher synthesis of anthocyanins. Recently, [34] reported that salicylic acid such as 2,4-D significantly increased the content of phenolic compounds in the calluses of Garcinia brasiliensis.…”
Section: Discussionmentioning
confidence: 98%
“…[7] also applied 2,4-D to determine the accumulation of anthocyanins in the cell culture of strawberries. 2,4-D appears to cause stress in plants and to increase the phenolic compounds synthesis [31,12] also reported that the medium supplemented with 2,4-D for the carrot callus initiation showed an increase in abscissic acid which resulted in a higher synthesis of anthocyanins. Recently, [34] reported that salicylic acid such as 2,4-D significantly increased the content of phenolic compounds in the calluses of Garcinia brasiliensis.…”
Section: Discussionmentioning
confidence: 98%
“…Reaction between radicals of ROS and different macromolecules e.g. lipoprotein, this process cause more rapid peroxidative damage which is evident from destruction of lipid membrane (108). Increased rate of electrolyte leakage has been used as an indicator of physical damage to cell membranes.…”
Section: Electrolyte Leakagementioning
confidence: 99%
“…The effects are generally short-term and the role of, for example, heating or commensal micro-organisms in producing the effects is unknown. Acute high dose rates have also been shown to affect a variety of seed constituents (e.g., Jan et al, 2012 ; Tilaki et al, 2015 ; Vaizogullar and Kara, 2016 ), which might affect subsequent germination and growth. In the field, soon after the Chernobyl NPP accident, dose rates around 2 mGy/h produced lethal embryo mutations in A. thaliana ( Abramov et al, 1992 ) and extensive studies of P. sylvestris near the Chernobyl NPP have shown that plants that received total doses of >2 Gy in areas of high short-term contamination had decreased reproductive ability and that this effect lasted for more than a decade ( Fedotov et al, 2006 ).…”
Section: The Effects Of Ionizing Radiation On Plantsmentioning
confidence: 99%